Exploring Correlation between Highway Intersection Capacity and Traffic Parameters - Sarwar, Samra; Sipos, Tibor; Bilal, Muhammad Tabish; Verebélyi, Bence (Periodica Polytechnica Transportation Engineering, 2021)
The key role of this research is a comparison between traditional strategic transport modelling of intersections of a road network with the real-time observed and calculated data. The significance of this research is to evaluate the traditional strategic transport modelling on mesoscopic level, which able to study the network level impacts of smaller traffic engineering and traffic management interventions in a precise way. This research attempts to quantify the correlation between highway intersection capacity and traffic parameters, for this there is a need to determine the capacity values of different node types. This situation gives rise to a question that is dealt with in this research. "How different traffic parameters can be interrelated with the capacity of intersections by using different simulations?". This paper used assignment procedure, and usage of real-time data set with the calibration of Budapest Transport Model. Five contiguous intersections are selected on a small section of road network and traffic data was collected on them. The intersections are simulated by the assignment of intersection capacity analysis (ICA) method. During analysis of traffic parameters, the actual values of saturation flow rate are quite different from the base model value, which results in different capacities of all nodes. Comparisons have been made between the travel times at zones, links, and nodes' levels while each comparison demonstrates a huge difference in actual traffic survey data model and base model. It has been concluded from the analysis that Budapest base transport model is very far from reality.